PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MTsN 3 SENGETI - Dani Damara, Achmad; Juliana, Rina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) model on student learning motivation in Islamic Religious Education subjects at MTsN 3 Sengeti. The background of this study is based on the low motivation of students in Islamic Religious Education learning which is characterized by low student activity, interest, and participation during the learning process. The Project Based Learning model is seen as one of the learning models that can increase student involvement through project activities that require collaboration, creativity, and problem solving. This study uses a quantitative approach with a correlational design to see the relationship between the application of the PjBL model and student learning motivation. The study population was all 205 students of class VIII MTsN 3 Sengeti. The sampling technique used stratified sampling with the Slovin formula so that a sample of 67 students was obtained. The research instrument used a Likert scale questionnaire to measure the application of the PjBL model and student learning motivation. Data analysis was carried out using simple linear regression analysis to determine the effect of independent variables on the dependent variable. The results of the study are expected to show that the application of the Project Based Learning model has a positive and significant influence on student learning motivation in Islamic Religious Education learning. Thus, the project-based learning model can be an alternative effective learning strategy in increasing student motivation and involvement in the learning process.